PERANAN TUMBUHAN LIAR DALAM KONSERVASI SERANGGA PENYERBUK ORDO HYMENOPTERA - Erniwati, Erniwati; Kahono, Sih (Jurnal Teknologi Lingkungan, 2009)
The role of the wild plants in relation to the conservation of the Indonesian insectpollinators was studied at several areas of Java. Three of direct observationmethods were applied: study of biodiversity and observation on the wild flowersand the insect pollinators as well, and the behaviour of the insects. The flowersof wild plants were relatively smaller and paler in colour, however they were moreattractive to insect pollinators than cultivated plants. Flowering time of the wildplants was mostly during wet seasons, contrary to that of the cultivated plantswhich was mostly during dry seasons. Our observation indicated that these wildplants are the food resources of insect pollinators during wet seasons. Observationdata support the importance of wild plants to supply food to insect pollinatorsduring wet seasons. Management of wild and cultivated plant environments isnecessary to conserve insect pollinators.